Breaking Free from Plastic: The Philippines' Journey Towards Sustainable Consumption and Production - De Guzman, Eduardo; Estaeban, Alfredo Jr. (Journal of Interdisciplinary Perspectives, 2024)
Plastic pollution presents a significant threat to global ecosystems, with the Philippines being a major contributor to ocean plastic waste. This environmental challenge endangers marine life, public health, and sustainability. The Philippines' No Plastic Policy is a strategic initiative aligned with Sustainable Development Goal (SDG) 12, which promotes responsible consumption and production. SDG 12 aims to enhance resource efficiency, develop sustainable infrastructure, and reduce waste through prevention, recycling, and reuse. This study examined the No Plastic Policy implementation progress in the Philippines, focusing on Cabanatuan City. Data were collected from 260 participants, primarily adults and females, using a quantitative descriptive research design. A researcher-made survey questionnaire facilitated data collection, which was analyzed using descriptive statistical tools. The findings indicate that residents largely adhere to the policy, motivated by the penalties imposed. However, challenges such as inefficient garbage collection, drainage maintenance issues, inadequate garbage trucks, and poor adoption of eco-friendly practices like using eco-bags persist. Despite the penal provisions, the study found that the penalties were not stringent enough to deter violations effectively. A comprehensive information campaign is necessary to improve waste management and disposal systems. The lack of funding was a critical barrier to systematic program management and implementation. Recommendations include enhanced enforcement, regular monitoring, and the promotion of biodegradable alternatives to strengthen policy efficacy. Stricter penalties and collaboration between barangay officials and local government units are essential for better compliance. The study underscores the importance of addressing the identified issues to optimize the impact of the No Plastic Policy, reduce plastic waste, and mitigate pollution. Future research should explore plastic waste management across various sectors to develop holistic, impactful solutions for local and national contexts.